Professional development in the digital age. Benefits and constraints of social media for lifelong learning - Maria Ranieri (Firenze University Press, 2019)
This paper presents an overview of reviews of the literature on the opportunities and constraints of social media use for professional development. The objective is to map the studies in the field to identify possible research gaps and, in tandem, to indicate future directions for effective and safe use of social platforms for lifelong learning. The study is based on Ebsco, WoS, Scopus and Google Scholar search, and on the adoption of explicit criteria for the selection of relevant studies, i.e. literature reviews published in English in peer-reviewed journals from 2009 to 2019 with a specific focus on social media for professional development. Thirteen pertinent studies were identified that were analysed with respect to the theme and nature of the reviews. The results of the selected studies were also coded in terms of benefits and constraints.   Lo sviluppo professionale nell'era digitale. Vantaggi e criticità dei social media per l'apprendimento permanente Il contributo presenta una rassegna delle revisioni della letteratura sulle opportunità e le criticità legate all'uso dei social media per lo sviluppo professionale. L'obiettivo è di mappare gli studi nel settore per individuare aree di ricerca ancora inesplorate e, parallelamente, indicare direzioni di sviluppo per l'uso efficace e sicuro delle piattaforme social per il lifelong learning. Lo studio si basa sull'interrogazione di Ebsco, WoS, Scopus e Google Scholar e sull'applicazione di criteri espliciti di selezione degli studi rilevanti, vale a dire revisioni della letteratura pubblicate in inglese su riviste referate nel periodo 2009-2019 con un focus specifico sui social media per lo sviluppo professionale. Sono stati individuati 13 studi significativi che sono stati analizzati rispetto al tema e alla natura delle rassegne. I risultati di tali studi sono stati poi codificati in termini di opportunità e criticità.